The Role of p38 MAPK in the Aetiopathogenesis of Psoriasis and Psoriatic Arthritis - Athanasios Mavropoulos; Eirini I. Rigopoulou; Christos Liaskos; Dimitrios P. Bogdanos; Lazaros I. Sakkas (Clinical and Developmental Immunology)
The pathogenetic mechanisms responsible for the induction of immune-mediated disorders, such as psoriasis, remain not well characterized. Molecular signaling pathways are not well described in psoriasis, as well as psoriatic arthritis, which is seen in up to 40% of patients with psoriasis. Signaling pathway defects have long been hypothesized to participate in the pathology of psoriasis, yet their implication in the altered psoriatic gene expression still remains unclear. Emerging data suggest a potential pathogenic role for mitogen activated protein kinases p38 (p38 MAPK) extracellular signal-regulated kinase 1/2 (ERK1/2), and c-Jun N-terminal kinase (JNK) in the development of psoriasis. The data are still limited, though, for psoriatic arthritis. This review discusses the current data suggesting a crucial role for p38 MAPK in the pathogenesis of these disorders.